Early Dental Identification and Multidisciplinary Management of Severe Pediatric Obstructive Sleep Apnea: A Case Report - Selsebil Laajimi; Rihab Mabrouk; Yamina Elelmi; Fatma Masmoudi; Ahlem Baaziz (International Journal of Advanced Health Science and Technology, 2026)
Pediatric obstructive sleep apnea (OSA) represents a significant yet often underdiagnosed respiratory disorder associated with adverse neurocognitive, cardiovascular, and developmental outcomes. Despite its clinical importance, early detection remains challenging, particularly in cases where symptoms overlap with common pediatric conditions. This study aims to highlight the critical role of pediatric dental assessment in the early identification and multidisciplinary management of severe OSA through a detailed case report. An 8-year-old male patient was referred for dental malpositions and molar-incisor hypomineralization. Comprehensive clinical, radiographic, and functional evaluations revealed craniofacial abnormalities indicative of airway obstruction. Screening using a validated pediatric questionnaire suggested OSA, which was subsequently confirmed by ventilatory polygraphy, demonstrating a severe apnea–hypopnea index (AHI) of 34.5 events/hour. A multidisciplinary treatment approach was implemented, including rapid maxillary expansion, mandibular advancement orthosis, nasal dilation, and myofunctional therapy. Due to limited access to polysomnography, follow-up relied on clinical observations and caregiver-reported outcomes. After six months, the patient exhibited notable improvements in respiratory function, sleep quality, and daytime alertness, along with enhanced facial aesthetics and oral function. These findings are consistent with existing evidence supporting orthodontic and functional interventions in managing pediatric OSA, particularly in cases associated with craniofacial abnormalities. In conclusion, this case underscores the pivotal role of pediatric dentists as frontline healthcare providers in recognizing early signs of OSA and initiating timely referrals. Integrating dental assessments into routine screening protocols can facilitate early diagnosis and coordinated multidisciplinary care, ultimately improving patient outcomes and preventing long-term complications.